Design resonant transformer - Mohd Faisal Ibrahim (School of Electrical System Engineering, University Malaysia Perlis, 2011)
This project aims to design a resonant transformer. A resonant transformer is basically an electromagnetic static equipment based on the principle of Faradays law of electromagnetic induction that can be generate high alternating voltages and current.